Mentoring in the Processing of Rejected Goods at a Timber Company in Semarang using Service Learning Approach - Ratnaningsih, Stephana Dyah Ayu; Endah, Sih Mirmaning Damar; Indarto, Stefani Lily; Hastuti, Theresia Dwi; Claudia, Gita (Journal of Innovation and Community Engagement, 2023)
This community service program was carried out at a family company in Semarang. The company's line of business is in wood processing. Initial observations showed that the problem in the company was due to the condition of the raw materials. Damaged, downsized, and rejected raw materials will occupy more space in the warehouse. This research aims to help the partner overcome the problem of raw materials. By using the service-learning method, the community engagement team consisting of lecturers, students, and company management discussed solutions that can be profitable for the company. The team found that further processing of the damaged raw materials was required. This process would turn the wasted material with low value into valuable pressed wood. According to the calculation of the reprocessing cost of this pressed wood, it can be classified as a profitable product. The team strongly recommends the company owner produce press wood continuously. In the long run, press wood will reduce inventory costs and increase revenue.